Stress+ – Towards an Open-Source Web Application for the Remote Induction of Acute Psychosocial Stress - Richer, Robert; Varkentin, Ekaterina; Kurmanbekova, Kurmanzhan; Müller, Victoria; Abel, Luca; Ringgold, Veronika; Küderle, Arne; Brich, Irina; Rohleder, Nicolas; Eskofier, Björn (2024)
Background It has been proposed that repeated exposure to acute stressors and the associated recurrent stimulation of stress pathways over a prolonged period of time promotes the transition from acute to chronic stress. Unfortunately, established laboratory stress protocols for acute psychosocial stress induction are only suitable for repeated use to a limited extent due to high demand for personnel and other resources, creating the need for novel stress protocols that can be conducted remotely and at a larger scale. Methods We introduce stress+, a browser-based web application for remote and repeated acute stress induction. stress+ offers a collection of screens and overlays which can be arranged into custom stress pipelines. This setup allows recreation and recombination of several components of established stress protocols to remotely induce acute psychosocial stress. Results A proof-of-concept study (N=403, 46.8±22.7 years, 55.3% women) revealed that the group exposed to stress via stress+ (N=183) showed a significantly higher perceived stress response compared to a control group (N=220), e.g., PANAS-Negative Affect (F[1, 401] = 68.14, p < 0.001, np2 = 0.15) and Visual Analogue Scale (F[1, 401] = 108.45, p < 0.001, np2 = 0.21). Conclusion While a validation of stress+ with biomarkers is still pending, our initial results suggest a successful remote stress induction that is comparable, or even superior, to previous work. By open-sourcing the stress+ framework, we encourage researchers to create their own acute stress induction pipelines and share their results with the communit